Conocimientos nutricionales de la madre y estado nutricional infantil en el distrito de San Juan de Miraflores en la ciudad de Lima, Perú 2012 - Herrera Sotero, Daniela (2014)
Background: Maternal nutritional knowledge may influence the development of chronic child malnutrition. Without previous investigations in Peru, this study seeks to find such an association. Methods: Cross-sectional study. Participants were mothers of San Juan de Miraflores accompanied by their children. Nutritional status was assessed using the WHO charts; level of nutritional knowledge through validated questionnaire (alpha de Cronbach=0.76). Logistic regression was used to measure association of knowledge, and other variables, with chronic malnutrition. Results: 150 mothers were surveyed, with age ranging between 19 and 56 (median of 30 years). 69.3% had high school education, 67.1% are cohabitants, and 75.5% are unemployed. Of 150 children, 8.7% had chronic malnutrition. We found that nutritional knowledge is inversely associated with child nutritional status (OR 0.28; p>0.05). We found association between the number of children and nutritional status (OR=2,06). Multivariate analysis showed that the knowledge maintained its association despite the consideration of the variable poverty. Interpretation: The prevalence of chronic malnutrition is similar to results found in Lima previously (ENDES 2011). The results demonstrate that nutritional knowledge is a protective factor against chronic malnutrition in the population studied. Knowledge may influence the nutritional attitudes and practices, leading to an appropriate nutritional status. There was association of chronic malnutrition with the number of children, and could be due to the decision of buying lower-quality food, or serve smaller portions. These results may be the basis for future studies.